A Study of the Use and Outcomes From Respiratory Viral Testing at a Mid-Sized Children's Hospital. (February 2019) - Zhu, Chelsea; Sidiki, Sabeen; Grider, Brittany; Fink, Brian; Hubbard, Nicole; Mukundan, Deepa
This study was a retrospective analysis of inpatient and emergency department (ED) data on respiratory pathogen panel (RPP) testing between December 16, 2013, and December 15, 2015, at a mid-sized children's hospital. We assessed whether RPP decreases antibiotic days of therapy and length of hospital stay for pediatric patients with acute respiratory infections. In the inpatient population, patients testing positive with RPP were given fewer antibiotic days of therapy (2.99 vs 4.30 days; P = .032) and had shorter hospital stays (2.84 vs 3.80 days; P = .055) than patients testing negative. In the ED population, patients testing positive with RPP received fewer discharge prescriptions for antibiotics than patients not tested (8.8% vs 41.1%; P < .001). RPP use was more prevalent in admitted patients than in ED patients (78.9% vs 7.3%; P < .001). Our results suggest that RPP testing curbs antibiotic use and decreases length of hospital stay.